Shoreline Dynamics in the Very Small Islands of Karimunjawa – Indonesia: A Preliminary Study - Alwi, Mulyadi; Mutaqin, Bachtiar W.; Marfai, Muh Aris (Geoplanning: Journal of Geomatics and Planning, 2023)
Indonesia is considered one of the biggest archipelagic countries in the world. According to some literature, Indonesia has more than 17,000 islands, most of which are classified as small islands. Some of these islands have become important areas for tourism, for instance, small islands in Karimunjawa. However, some of these islands experienced shoreline changes caused by erosion and accretion. Hence, this research aims to map the spatial distribution of shoreline change using the Digital Shoreline Analysis System (DSAS) add-in on ArcGIS. The primary dataset utilized as input consists of Sentinel 2A imagery captured over 2017 and 2022. The results showed that around 89 segments, or 51.47% of the total shoreline segments, tend to experience accretion, while the remaining 79 segments, or 45.93%, experience erosion. This finding suggests that most shoreline segments tend to accrete or seaward movement in the research area. The results of this study exhibit notable disparities when compared to the occurrences observed in Pandeglang (Banten), Kuwaru (Yogyakarta), Buleleng (Bali), and East Java Province, where coastal erosion prevails over accretion. The managers of the islands try to reduce the threat of erosion by constructing dykes and breakwaters. However, these buildings are ineffective due to the relatively simple structures and building materials. Therefore, further studies are needed to determine the type and specification of mitigation buildings that are suitable for implementation in that location.